ANALISIS FAKTOR YANG MEMENGARUHI PRODUKSI KACANG METE DI KECAMATAN KUBU KABUPATEN KARANGASEM - Mulyawati, Ni Wayan; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Plantation is one of potential sectors for development. One of sectors is cashew. This commodity has a high economic value, because not only can it be used directly by farmers, cashews also have export value so that this can bring foreign exchange to the State. The purpose this study was to analyze influence of land area, labor, and capital on the production of cashews in Kubu District, Karangasem Regency. The number of samples taken was 158 farmers using the Proportionate Stratified Random Sampling method. Data collection is done by structured interviews, in-depth interviews, and observations. The analysis technique used is multiple linear regression in the form of Cobb-Douglas production function. The results of the study stated that the area of ??land, labor, and capital simultaneously had a significant effect on the production of cashews in Kubu District, Karangasem Regency. Partially, land area, labor and capital partially have a significant positive effect on cashew nut production in Kubu District, Karangasem Regency. The economies of scale in cashew farming in Kubu District, Karangasem Regency are in a condition of increasing return to scale. But partially independent variables are in a decreasing return to scale condition. Keywords : Production, land area, labor, capital